2015
DOI: 10.1016/j.molcel.2015.07.015
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Adaptor SLP-76 Binds to SUMO-RANGAP1 at Nuclear Pore Complex Filaments to Regulate Nuclear Import of Transcription Factors in T Cells

Abstract: SummaryWhile immune cell adaptors regulate proximal T cell signaling, direct regulation of the nuclear pore complex (NPC) has not been reported. NPC has cytoplasmic filaments composed of RanGAP1 and RanBP2 with the potential to interact with cytoplasmic mediators. Here, we show that the immune cell adaptor SLP-76 binds directly to SUMO-RanGAP1 of cytoplasmic fibrils of the NPC, and that this interaction is needed for optimal NFATc1 and NF-κB p65 nuclear entry in T cells. Transmission electron microscopy showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 62 publications
0
33
0
Order By: Relevance
“…Jurkat T cells and murine T cell hybridoma DC27.10 and 2B4 cells were maintained in RPMI 1640 medium supplemented with 5% (v/v) FBS (Sigma) and 100 U/ml penicillin/streptomycin (29). Total CD4 + T cells were enriched from primary T cells from 6 to 8-wk-old female C57BL/6J mice (Shanghai Laboratory Animal Center, Shanghai, China) with mouse CD4 + enrichment selection column (R&D System) according to the manufacturer's manual.…”
Section: Cell Culture and Reagentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Jurkat T cells and murine T cell hybridoma DC27.10 and 2B4 cells were maintained in RPMI 1640 medium supplemented with 5% (v/v) FBS (Sigma) and 100 U/ml penicillin/streptomycin (29). Total CD4 + T cells were enriched from primary T cells from 6 to 8-wk-old female C57BL/6J mice (Shanghai Laboratory Animal Center, Shanghai, China) with mouse CD4 + enrichment selection column (R&D System) according to the manufacturer's manual.…”
Section: Cell Culture and Reagentsmentioning
confidence: 99%
“…Cells were incubated with fluorescence-labeled Abs (BD Biosciences) for 1 h at room temperature in FACS buffer (0.5% BSA in PBS), washed three times with PBS, and resuspended into FACS buffer. Analyses were performed using a FACSCalibur flow cytometer (BD Biosciences) as described before (29). For the intracellular Ca 2+ measurement, cells were loaded with 5 mM of Indo-1-AM (Thermo Fisher) in RPMI 1640 and incubated for 1 h at 37˚C.…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Gads may directly influence transcriptional events via the ability of SLP-76 to translocate to the nuclear pores, where it regulates the nuclear translocation NFκB [86]. It remains to be seen whether this activity depends on Itk-targeted phosphorylation sites on the adaptors.…”
Section: The Itk-targeted Sites On Slp-76 and Gads Are Selectively Rementioning
confidence: 99%
“…Further studies have suggested that Nup210 is acting as a scaffolding protein for transcriptional complexes such as Mef2C, and that the tissue-specific expression is most likely a driver for the specialization of NPCs in different cell types, thereby playing a role in the regulation of cell fate ( 17 ). The regulatory role of the NPC in the import of transcription factors in T cells in the context of inflammation and immunity has been shown in a number of studies ( 18 21 ), and this cellular function has also been studied in detail in myocyte culture ( 17 ), however the role of NUP210 at the organism level has not previously been studied.…”
Section: Introductionmentioning
confidence: 99%